The Utilization of Village Land for the Enhancement of Community Welfare in Tibubiu Village, Kerambitan District, Tabanan Regency, Bali Province - I Made Pria Dharsana; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar; I Nyoman Gede Sugiartha; Anak Agung Sagung Laksmi Dewi; I Made Ardena (Community Service Journal of Law, 2024)
Tourism is a key business sector that countries must continue to develop, as it has proven to significantly contribute to foreign exchange. A well-developed tourism sector can attract both Indonesian tourists (wisnus) and foreign tourists. The influx of visitors can also stimulate investors' interest in investing their capital in tourist villages. Community service activities can involve providing various legal information and offering legal counseling and consultations to the community, particularly in agrarian law. One important aspect to consider is the understanding of legal principles within the Tibubiu Village environment, where it's hoped that every Banjar Customary Environment comprehends the use of village land and the legal implications it entails. To enhance knowledge and address issues arising from village land use and management, it's essential to communicate more in-depth and consistent information regarding the effects of village land utilization. Through this community service initiative, the Tibubiu village community can gain awareness of and articulate the implications of using village land in ways that do not comply with existing laws.